A comparison of currently available optoelectronic motion capture systems - Topley, M.; Richards, J. G. (Journal of Biomechanics, 2020)
The measurement of human motion relies heavily on the ability of the optoelectronic motion capture systems to accurately measure retroreflective marker positions. Marker position accuracy is largely dependent on the optical characteristics of the camera system and algorithms implemented in the tracking software. In 1999, Richards critically reviewed multiple camera systems and each of their ability to generate the same marker coordinate positions under different field tests. Field tests were designed utilizing what became to be known as the Standard Assessment of Motion System Accuracy (SAMSA) device. The SAMSA test results indicated that some systems outperformed others and accuracy varied depending on the test. In the subsequent 20 years, motion capture technology has significantly improved. Therefore, we aimed to replicate the tests from 1999 using current, higher-resolution motion capture systems and current calibration techniques. Reference marker distances were established utilizing a FaroArm 3D digitizer (FARO technologies). The modern cameras field test performance showed nearly a three-fold improvement in agreement with the reference measure compared to their 1999 predecessors. No systems` absolute marker distance measured greater than 0.5 mm from the FaroArm measurement and no systems` maximum error exceeded 1.0 mm. Given the consistency in accuracy reported by all the systems included in the current assessment, it`s reasonable to assume that the current systems would eliminate errors associated with system hardware/software as an obstacle to sharing data between laboratories.